Karakter Dan Pola Tata Ruang Kawasan Sekitar Kampus Universitas Brawijya - Ramdlani, Subhan; Soekirno, Ali; Sri Giriwati, Novi Sunu (Jurnal Ruas, 2013)
The Surrounding of UB campus are an area affected directly or indirectly by the development of UB. The developments of the campus will be more or less influence to the spatial development of this area. Conversely, the dynamics that occur in this area will be an important input in the development of the upcoming campus. From this point, the purpose of this study was to identify the characteristics and spatial surrounding area of UB campus as patterns of land use that fit by the character. By studying and understanding the existing conditions, the results are expected to be used as one of the